2019
DOI: 10.2147/cmar.s188903
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of taste and smell training on taste disorders during chemotherapy – TASTE trial</p>

Abstract: Purpose Two-thirds of cancer patients report taste disorders during and after chemotherapy. Taste disorders impact on nutritional status which is highly relevant for treatment efficacy and overall prognosis. Improvement of taste disorder is of particular importance for cancer patients’ outcomes, thus the TASTE trial was conducted to improve taste disorders with a taste and smell training. Methods In this trial, patients undergoing chemotherapy were screened for taste di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
(25 reference statements)
0
23
0
8
Order By: Relevance
“…Taste changes occur in up to 84% of patients undergoing chemotherapy treatments [ 131 ]. Recent studies report that taste disorders were more frequent in gastrointestinal than in breast cancer patients [ 132 ]. Patients who experience gastrointestinal symptoms during chemotherapy are also associated with an increased odd of having taste perception changes [ 133 ].…”
Section: Clinical Implication Of Microbiota/taste Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taste changes occur in up to 84% of patients undergoing chemotherapy treatments [ 131 ]. Recent studies report that taste disorders were more frequent in gastrointestinal than in breast cancer patients [ 132 ]. Patients who experience gastrointestinal symptoms during chemotherapy are also associated with an increased odd of having taste perception changes [ 133 ].…”
Section: Clinical Implication Of Microbiota/taste Interactionsmentioning
confidence: 99%
“…Indeed, oral mucositis is closely associated with alterations in taste and frequently reported in cancer patients undergoing chemotherapy [ 136 ]. While re-establishment of the microbiota in cancer patients has yet to be explored as a therapeutic treatment for taste dysfunctions, intensified nutritional counseling with taste and smell training has been shown to improve taste perception in these patients [ 132 ]. It should also be noted that many prescription and non-prescription drugs, including antibiotics, angiotensin-converting enzyme inhibitors, lipid-lowering agents, proton pump inhibitors, chemotherapy drugs, and metformin are known to affect taste as well as disrupt the gut microbiota.…”
Section: Clinical Implication Of Microbiota/taste Interactionsmentioning
confidence: 99%
“…A recent trial showed that a smell and taste training during chemotherapy, including actively tasting and smelling foods and odors on daily basis over the course of several weeks, can improve gustatory function in patients with changes in gustatory function. However, this did not directly improve quality of life or decrease the risk of malnutrition [44]. As changes in gustatory function can lead to a reduced energy intake [45], it would be highly relevant to investigate the relation between this training and dietary intake, which was not included in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…focused on novel interventions to improve taste and smell. No guidelines for the treatment of smell and taste disorders are available, with general nutritional counselling that is offered to patients not earnestly addressing this subject (20). Table 4 provides the summary of interventions to prevent or treat TSAs in lung cancer patients, included in the review.…”
Section: Management and Treatment Of Taste And Smell Alterationsmentioning
confidence: 99%